ZSM-5-Confined Fe-O4 Nanozymes Enable the Identification of Intrinsic Active Sites in POD-like Reactions - Gaolei Xu; Yunfei Wu; Guanming Zhai; Huibin Ge (Nanomaterials)
As widely used peroxidase-like nanozymes, Fe-based nanozymes still suffer from an unclear reaction mechanism, which limits their further application. In this work, through alkaline treatment and then the replacement or occupation of strong acid sites by isolated Fe species, porous ZSM-5-confined atomic Fe species nanozymes with separated medium acid sites (Al-OH) and isolated Fe-O4 sites were prepared. And the structure and the state of Fe-O4 confined by ZSM-5 were determined by AC-HAADF-STEM, XPS, and XAS. In the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by the hydrogen peroxide (H2O2) process, the heterolysis of H2O2 to ∙OH mainly occurs at the isolated Fe-O4 sites, and then the generated ∙OH can spill over to the Al-OH sites to oxidize the adsorbed TMB. The synergistic effect between Fe-O4 sites and medium acid sites can significantly benefit the catalytic performance of Fe-based nanozymes.